(untitled) (Pedagogy of Higher and Secondary Education, 2003)
Clause is devoted to a problem application of perspective systems in educational art practice of the students. The author marks existence of large number of visual positions in fine art. The opportunity of application of excellent (different) composite receptions (point of view) in educational composite practice is considered (examined) as against linear prospect, dominant in art pedagogic. The work includes samples o f construction o f the image not only with excellent (different) visual positions, but also with association o f the several points o f view in a composition. Clause is designed both fo r the students o f an art structure, and on the teachers o f maximum pedagogical school, art schools etc..